Motivación y desempeño docente - Quispe, Bacilia; Coacalla-Castillo, Carlos; Lima, María; Marcilla, Hector; Suarez, Arturo; Condori, Juan (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the Micaela Bastidas National University of Apurímac, whose main objective was to determine the level of association of motivation with job performance from the perspective of the teacher of the Public Educational Institutions of the Initial Level of Tamburco (Peru). The study was developed following the process of basic research at the associative correlational level. The data of each one of the variables was registered in the motivation questionnaires that I consider three dimensions (need for achievement, need for power and need for affiliation) and teaching performance also with three dimensions (Planning of pedagogical work, management of learning processes). teaching - learning and professional responsibilities). We worked with all the teachers of the initial level of Tamburco. The statistical treatment according to the research design for testing the selected hypothesis was Kendall's Tau_b coefficient, which allowed reaching the inferential conclusion that there is an association between motivation and teaching performance. On the other hand, in a descriptive way, it is concluded that 16 teachers of 29 individuals in the sample indicate that they do not care about taking into account the needs of achievement, power or affiliation as a motivating force, and in terms of teaching performance, 23 teachers present attitudes and behaviors that reflected that they almost never plan the pedagogical work, nor the management of the teaching and learning processes is low, 5 teachers sometimes participate in their professional responsibilities and only one teacher usually plans, manages the pedagogical processes and assumes their professional responsibilities.